Sufis entangled: traveling Tariqa - ten years down the road into Sufis entangled - Ettmüller, Eliane; Ewald, Sarah; Kramer, Max (Dastavezi, 2021)
While revisiting the film Sufis Entangled ten years after its release, the three filmmakers engage in questions of production, form, and historical context. The essays that constitute this piece flesh out the intricate ways how cultural-religious conflicts are enmeshed in the material realities of the filmmaking process.